Thematic Network of Challenges in Project Fund Financing and Proposed Solutions - Milad Easaei; Mohammad Tohidi; Mohammad Mahdi Fereydooni (Journal of Asset Management and Financing)
Financial instruments in the capital market, such as debt and equity financing tools, along with the establishment of funds, play a pivotal role in advancing financing methods, ensuring timely project execution, and the successful completion of infrastructure projects. Despite their potential, project funds—an innovative financing method in the capital market—have not gained widespread acceptance. This study aims to conduct a diagnostic analysis of the current model of project financing through project funds and propose corrective solutions. Employing a qualitative approach, this research is categorized as applied in terms of objectives and descriptive-survey in terms of data collection. Through document analysis (reviewing books, articles, and notes) and expert interviews, the challenges associated with financing via project funds were identified and categorized into three main themes: process and structural challenges, environmental challenges, and legal and regulatory challenges. Drawing on international experiences, corresponding solutions were proposed, including the facilitation of laws and regulations, revision of the project fund's charter, and reconsideration of corporate governance practices.Keywords: Project Fund, Financing, Financing Funds, Capital Market.JEL Classification: O16, G32, G23 IntroductionProject financing has been extensively studied, yet specialized research on financing through project funds remains limited. Most existing studies focus on the financial capacity of these instruments within the capital market, with only a few exploring their structure and integration with other financing tools. Notably, no study has comprehensively addressed the challenges and corrective measures for project funds in Iran's capital market. Project funds, as financial engineering instruments, aim to facilitate project financing in the capital market. However, since their introduction in 2017, they have seen limited implementation. In contrast, leading countries typically finance projects through private equity investment funds and by offering project company shares in the capital market. This study seeks to identify the challenges of project financing via project funds and propose solutions based on insights from capital market experts and international best practices. Materials & MethodsData were collected through document analysis, including reviews of books, articles, reports, and expert interviews. Purposive sampling was employed, selecting nine experts based on their expertise, educational background, and professional experience. Thematic analysis, following the Attride-Stirling (2001) approach, was conducted at three levels: basic themes, organizing themes, and global themes. This method identified 52 key statements and 11 basic themes, which were categorized into three organizing themes and one global theme. The findings were validated by a focus group comprising a university faculty member, experts, and managers from the Securities and Exchange Organization's Research Center, ensuring credibility and reliability.FindingsThe thematic analysis revealed that the global theme is "challenges in financing through project funds." The process and structural challenges encompass 7 basic themes, the environmental challenges consist of two basic themes, and finally, the legal and regulatory challenges include two basic themes. Discussion & ConclusionThis paper examines project financing through the establishment of project funds, addressing its operational, legal, and regulatory aspects. While project funds hold significant potential for financing projects in the capital market, their adoption has been limited, with only one instance of utilization to date, primarily due to structural deficiencies and fundamental challenges. To address these issues, this study proposes targeted solutions categorized into three areas: (1) process and structural challenges, including centralizing financial resources under the fund manager, setting a defined lifespan for the fund with penalties and incentives, revising the technical supervisory entity's responsibilities, reconsidering mandatory underwriting and market-making requirements, incorporating preferred shares, and separating the boards of the project fund and project company; (2) environmental challenges, such as encouraging active government participation, facilitating fund establishment through regulatory support, and increasing investor participation via specialized investment funds; and (3) legal and regulatory challenges, with the most critical solution being the strengthening of the legal and regulatory framework to ensure clarity and reduce uncertainties in the operation of project funds. These solutions are elaborated using a descriptive-analytical approach to provide a comprehensive roadmap for improving the adoption and effectiveness of project funds.